Directed technological change, energy and more: a modern story - Zheng, H.; Roseta-Palma, C.; Ramalho, J. J. S. (Environment and Development Economics, 2020)
Reliance of modern economic activities on the use of energy, most of which still comes from non-renewable sources, provokes concerns regarding the most efficient utilization of energy inputs in production. While most theory expects directed technological change to be biased towards the non-renewable input, there is rare macro-level evidence that technological change is actually biased towards energy rather than other main inputs. To fill this gap, we apply stochastic frontier analysis to country data regarding output produced with capital, labor and energy, and estimate a set of indicators for technological change.Findings show that technological change is biased the most towards energy in general. In particular, although different groups of countries exhibit various patterns, there is strong evidence that technological change favors energy more than labor.This is in line with the theoretical expectation that technological change ought to be biased towards the non-renewable input rather than the renewable ones.